Cutaneous parasitism in patients with American visceral leishmaniasis in an endemic area - Moura,Carla Riama Lopes de Pádua (2020)
Abstract INTRODUCTION: Visceral leishmaniasis (VL) represents a public health concern in several areas of the world. In the American continent, VL transmission is typically zoonotic, but humans with active VL caused by Leishmania infantum are able to infect sandflies. Thus, individuals with cutaneous parasitic infections may act as reservoirs and allow interhuman transmission. Additionally, the skin may be responsible for reactivation of the disease after therapy. This study’s objective was to evaluate cutaneous parasitism in humans with VL in an American endemic area. METHODS: A cross-sectional hospital-based study was conducted in northeast Brazil from October 2016 to April 2017. Biopsies of healthy skin for histopathology and immunohistochemistry were performed prior to treatment in all study patients. RESULTS: Twenty-two patients between the ages of five months to 78 years were included in the study. Seven patients (31.8%) tested positive for HIV. Only one patient had cutaneous parasitism, as confirmed by immunohistochemistry prior to treatment. Parasitism was not detected after treatment. CONCLUSIONS: Cutaneous parasitism in the healthy skin of humans with visceral leishmaniasis, although unusual, may be a source of infection for phlebotomine sandflies.